Ocupo, logo existo: ocupações secundaristas e o tecer de outra educação possível - Barbosa, Fernanda Ströher (2018)
The track of this work provokes one of the possible meetings with the Brazilian Secondary Occupations. Following the voices of women leaders, it seeks to trace the attention and learning qualities of the Occupation state in bodies and in the environment. It aims to analyze, through participant observation and interviews, the school space as a catalyst for the crisis, in dispute for the ways of living, knowing, producing itself and the world, in which crossbreeding between anthropology, education, production of subjectivity and cognitive policies. The analysis of the pedagogical and cultural dynamics of the political and social movement developed in the work from three figures proposed by Tim Ingold: the trails, the tracks and the meetings. In traces, the vestiges of the new possibilities to exist apprentice, tutor and school that come together as new ways of being girl. In the lines of life, the pulse of the territories that are formed in the cross between the movements of women's rights, childhood and youth and the struggle for public education, in dispute in the crisis between the modes of self-government and others. In the meetings, we elaborate via body the collective event of the crisis and the conceptual reverberations that are given by the abandonment of the identity statute and by the production of the common, the difference and autonomy in the reorganization of the social and scholastic life. As a result of the analysis, a specific form of learning arises that goes back to the Latin American indigenous movements, related to the immersion time that characterized the occupation and to the state of constant attention and with a varied focus, listening to otherness through articulation spaces politics of the knowledge and abilities of caring for oneself, others and space. Moreover, the senses provoked in the occupying experience of the school as a political space prologue until the appropriation of political figures in the production of subjectivity among adolescents in the reintegrated school. I close thematizing the feminist movement as a historical and social condition for the strengthening of women's leadership and for the development of "problematization" and "deconstruction" skills, which make the debate about the production and representation of female subjects and another possible school coincide.